2008
DOI: 10.1002/aqc.1015
|View full text |Cite
|
Sign up to set email alerts
|

Survival rates for a declining population of bottlenose dolphins in Doubtful Sound, New Zealand: an information theoretic approach to assessing the role of human impacts

Abstract: ABSTRACT1. The bottlenose dolphins of Doubtful Sound, New Zealand are a declining population at the southern limit of the species' range, exposed to impacts from tourism and habitat modification. Patterns in apparent annual survival were analysed from photographic resightings of naturally marked adults (1990 to 2008) and calves within the first year of life (1994 to 2008) using capture-recapture models.2. The most parsimonious model for adults provided a time-invariant, sex-invariant estimate of survival (j a(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
117
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(133 citation statements)
references
References 69 publications
15
117
1
Order By: Relevance
“…Conversely, demographic approaches also provide quantitative predictions of future population trends and extinction risk that can inform precautionary management (Harwood, 2000;Lacy, 1993;Thompson et al, 2000;Fujiwara and Caswell, 2001). Comparative study of rate of decline or risk of extinction between different scenarios of anthropogenic impact using a demographic framework (Moore and Read, 2008;Currey et al, 2009b) can also quantify how uncontrolled environment deterioration may impact long-term survival of threatened populations.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, demographic approaches also provide quantitative predictions of future population trends and extinction risk that can inform precautionary management (Harwood, 2000;Lacy, 1993;Thompson et al, 2000;Fujiwara and Caswell, 2001). Comparative study of rate of decline or risk of extinction between different scenarios of anthropogenic impact using a demographic framework (Moore and Read, 2008;Currey et al, 2009b) can also quantify how uncontrolled environment deterioration may impact long-term survival of threatened populations.…”
Section: Introductionmentioning
confidence: 99%
“…Continued photo-iD monitoring of the population will be essential to assess future trends in calf and adult survival. elthough declining survival of calves is most likely driving the population decline in Doubtful Sound (Currey et al 2008), it is important to establish if emigration to other fiords is a contributing factor. Bottlenose dolphins are highly social animals and migrant dolphins could increase their chances of survival by joining an established bottlenose dolphin population (Connor & Norris 1982).…”
Section: Discussionmentioning
confidence: 99%
“…Coincident with the population decline, the survival of newborn calves decreased from 0.800 before 2000 (Haase & Schneider 2001), to 0.569 (CV = 30%) between and 2007(Currey et al 2007. Preliminary modelling of a long-term data set suaaests that this decline occurred around 2002 Fiordland, New Zealand. and that current levels of calf survival are, to our knowledge, the lowest calf survival rates reported in the literature (Currey et al 2008). The rate of decline in abundance and survival is unsustainable and long-term viability of the population is threatened (Lusseau et al 2006;Currey et al 2007Currey et al , 2008.…”
Section: Introductionmentioning
confidence: 97%
“…The studies record the occurrence of each identified dolphin in the study area and whether or not they were accompanied by calves. We focused on the sighting history of calves that were consistently associated with the same female [39], because we anticipated that disturbance was more likely to affect calf survival rather than female pregnancy rate [40,41]. Details of the photo-identification data collection are provided in [26,27,37].…”
Section: (B) a Multi-stage Model For Calf Survivalmentioning
confidence: 99%